Impact of minimally invasive root canal treatment on healing outcomes in a randomized clinical trial - Seung-Kyung Kwon; Minkyeong Seog; Dohyun Kim; Il-Young Jung (Scientific Reports)
Abstract Minimally invasive endodontic treatment has been an important topic of discussion in recent years, particularly in endodontics. This randomized prospective clinical trial aimed to assess outcomes after at least 2 years following two distinct root canal treatment (RCT) protocols: (1) conventional treatment protocol (CP) and (2) minimally invasive protocol (MP), with a focus on the amount of root canal preparation. 175 mature permanent teeth were randomly assigned to one of two groups. The CP group was treated using ProTaper Gold systems and the continuous wave condensation technique, while the MP group underwent treatment with TruNatomy, ultrasonic-associated irrigation, calcium hydroxide (Ca[OH]₂), and a sealer-based obturation technique. The patients were recalled after a minimum of 2 years, and the outcome was dichotomized into success or failure according to strict and loose criteria, respectively. The results were analyzed statistically through chi-squared, Fisher’s exact tests or t-tests, followed by multivariable logistic regression analysis. A total of 125 teeth were analyzed, with a recall rate of 67.4% and an average follow-up period of 36 months (24–46 months). The overall success rates were 84.8% for loose criteria (CP 91.9%, MP 77.8%) and 80.8% for strict criteria (CP 88.7%, MP 71.4%), with statistically significant differences observed between the groups (p = 0.027 and p = 0.016, respectively). The MP group and the presence of sinus tract were associated with a greater risk of failure under both loose and strict criteria. Within the constraints of this protocol—which combined minimal preparation with supplemental disinfection techniques—the MP group exhibited significantly lower success rates than the CP group. While MP may offer benefits in structural preservation, clinicians should carefully weigh these advantages against the potential compromise in treatment outcomes. Trial registration: CRIS, KCT0005351. Registered on 25 August 2020.